(3dWGFa GdETGQGJ aj MbGFb GdYHGQGJs - (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM bdhH ChdjGFg dYQaGJg hChVM fgL GdMb s
(3BNQgG (B:s
(3hdG jTcQ UfGYJg hjSjQ ef Mhdg hbhfg hjbGd GdYed GdUGdM hGYJbGO LhGO (B,(3GdMeO ddg s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1551s
Keywords: (3GdJaSjQ hYdhe GdbQBfs